The role of digital health literacy in shaping nurses’ self-efficacy and innovative work behavior: A cross-sectional study - Doaa Abd El-Fattah Mousa Edrees; Amal Hamdy Abou Ramadan; Fatma Zaghloul Mahmoud; Ahmed Mansour Almansour; Moataz Maged; Mohamed Gamal Mostafa (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: In the evolving digital healthcare landscape, nurses are required to adapt to emerging technologies and demonstrate digital health literacy (DHL) to ensure high-quality patient care. DHL may enhance nurses’ self-efficacy (SE) and foster innovative work behavior (IWB), both of which are essential for professional development and healthcare innovation. Objective: This study aimed to explore the role of digital health literacy in shaping nurses’ self-efficacy and innovative work behavior. Methods: A cross-sectional correlational study was conducted among all available intensive care unit nurses (N = 406) at two university-affiliated hospitals in Egypt. Data were collected between November 2024 and January 2025 using three validated instruments: The Digital Health Literacy Instrument (DHLI), the General Self-Efficacy Scale (GSE), and the Innovative Work Behavior Scale (IWBS). Data analysis included descriptive statistics, Pearson correlation, and multivariate linear regressions. A mediation analysis was further conducted to evaluate the role of self-efficacy in the relationship between digital health literacy and innovative work behavior. Results: Nurses reported a mean digital health literacy score of 68.34 ± 10.61 (75.14% of the maximum possible score). The mean self-efficacy score was (32.36 ± 6.30). Approximately 66% of participants exhibited relatively high scores of innovative work behavior, particularly in the domains of idea generation and implementation. Statistically significant positive correlations were found between DHL and SE (r = 0.688, p < 0.001), DHL and IWB (r = 0.484, p < 0.001), and SE and IWB (r = 0.674, p < 0.001). An adjusted mediation analysis showed that DHL was positively associated with SE (B = 0.443, β = 0.688, p < 0.001, R² = 0.565) and with IWB in the total effect model (B = 0.453, p < 0.001). SE was also positively associated with IWB (B = 0.787, β = 0.604, p < 0.001). After inclusion of SE in the mediation model, the direct effect of DHL on innovative work behavior remained significant. The final mediation model explained 54.8% of the variance in innovative work behavior (R² = 0.548), after controlling for hospital type, age, and department. Mediation analysis indicated that SE partially mediated the association between DHL and IWB. Conclusion: Digital health literacy was positively associated with nurses’ self-efficacy and innovative work behavior, with self-efficacy partially mediating the association within the tested model. These findings suggest that integrating DHL into continuous professional development and nursing curricula may be beneficial to support digital transformation in healthcare.